Virginia Woolf and nineteenth-century women writers : Victorian legacies and literary afterlives - Reus, Anne (Edinburgh : Edinburgh University Press, 2022)
This book examines Virginia Woolf's influence on the literary afterlives of nineteenth-century women of letters including Jane Austen, Mary Russell Mitford, Elizabeth Barrett Browning, Charlotte Brontë, George Eliot, Margaret Oliphant and Mary Augusta Ward through her journalism. Woolf's responses to her literary predecessors provide new insights into her self-positioning within the literary canon and the interplay of biographical innovation and Victorian legacies in her non-fiction. This study demonstrates that Victorian narratives and tropes of female professionalism continue to shape Woolf's representations of nineteenth-century women writers even at the heyday of her Modernist fame. It contextualizes the overt feminism of A Room of One's Own within Woolf's more ambiguous literary biography to argue for its status as a transitional, post-Victorian body of work.
1. Introduction: Rainbow and granite, women and biography -- 2. 'Vain are these speculations' : Jane Austen and female perfection -- 3. 'Even a lady sometimes raises her voice' : Mary Russell Mitford and Elizabeth Barrett Browning -- 4. 'That indefinable something' : Charlotte Brontë and protest -- 5. 'A gap in your library, Madam' : the lives of professional women -- 6. Writing Virginia Woolf : autobiographical fragments.
Includes bibliographical references and index.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2022).
eBooks on EBSCOhost
Keywords: Woolf, Virginia, -- 1882-1941.; Woolf, Virginia, -- 1882-1941; Literature -- Women authors -- History and criticism; Literature, Modern -- 19th century -- History and criticism; Literary Studies; Écrits de femmes -- Histoire et critique; Littérature -- 19e siècle -- Histoire et critique; LITERARY CRITICISM / Feminist; ART / Criticism & Theory; Literature, Modern; Literature -- Women authors; Literature: history & criticism; Literary studies: general; Literary studies: fiction, novelists & prose writers; Literature; 1800-1899; Criticism, interpretation, etc